2003
DOI: 10.1002/bem.10100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coexposure to 50 Hz magnetic fields and an aneugen on human lymphocytes, determined by the cytokinesis block micronucleus assay

Abstract: Interference of 50 Hz extremely low frequency magnetic fields (ELF-MF) with the known aneugen vinblastine (VBL) on micronucleus formation was tested with the in vitro cytokinesis block micronucleus assay in human lymphocyte cultures. Isolated lymphocyte cultures were prepared from 18 individuals. Three groups of quadruplicate cultures from six unrelated individuals were exposed to 50 Hz ELF-MF of background (bkg), 80 and 800 microT, respectively, during the complete incubation period (72 h). Twenty-four hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…In the latter, Ding et al (2003) found that a 5 mT, 60 Hz magnetic field significantly increased CREST (Calcinosis, Raynaud's phenomenon, Esophageal dismotility, Sclerodactility, Telangectasia)-positive micronuclei in CHO cells after exposure to X-rays. Verheyen et al (2003) detected a significant increase of micronuclei (without distinguishing between CREST-positive and -negative) in human lymphocytes exposed to vinblastine and 80 or 800 mT. Mailhes et al (1997), instead, found an increase in hyperploidy in murine oocytes.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the latter, Ding et al (2003) found that a 5 mT, 60 Hz magnetic field significantly increased CREST (Calcinosis, Raynaud's phenomenon, Esophageal dismotility, Sclerodactility, Telangectasia)-positive micronuclei in CHO cells after exposure to X-rays. Verheyen et al (2003) detected a significant increase of micronuclei (without distinguishing between CREST-positive and -negative) in human lymphocytes exposed to vinblastine and 80 or 800 mT. Mailhes et al (1997), instead, found an increase in hyperploidy in murine oocytes.…”
Section: Introductionmentioning
confidence: 92%
“…On the other hand, other works have detected positive results only in conditions of co-exposure with other mutagenic agents, such as static magnetic fields (Tofani et al 1995, benzopyrene (Cho & Chung 2003, Moretti et al 2005, X-rays (Ding et al 2003) and vinblastine (Verheyen et al 2003). These results led to the hypothesis that ELF magnetic fields are able to enhance, but not to start, a mutagenic event.…”
Section: Introductionmentioning
confidence: 98%
“…Magnetic water were induced a significant increase in Hb in lambs, ewes and in fish [44][45][46]. Treatment with magnetic water caused a high potential in the processing of the body's cells and tissues of different nutrition appropriate to perform its best of its biological, leading to the lifting capacity of organs and tissues hematopoietic like liver, kidney and spleen, to produce blood [4,33,47]. Also due to increase in metabolic reactions in the tissues, raising hormone which works to increase the production of RBC and thus increases PCV [4,48,49].…”
Section: Effect Of Magnetic Water On Haematological Parametersmentioning
confidence: 99%
“…A replication study is not completely terminated but as far as we can tell at present the results appear to be largely identical. It should be realized yet that ELF-MF's-induced micronuclei (possibly due to aneuploidy) were not found in one of our earlier studies [24] as well as in some other investigations [19]. An explanation may be that cells that are not in optimal condition are more susceptible to ELF-MF-induced genetic alterations.…”
Section: Discussionmentioning
confidence: 48%
“…Effects were for example found when ELF's were used as cofactors that modify cellular responses to other agents, e.g. static fields [21], benzopyrene [22], benzene [23], vinblastine [24,25], and X-rays [25]. According to these studies ELF-magnetic fields are thus able to enhance, but not to start a mutagenic (DNA damaging) effect.…”
Section: Introductionmentioning
confidence: 98%